Penerapan Metode Pembelajaran Show and Tell pada Materi Iklan untuk Meningkatkan Keterampilan Berbicara Siswa Kelas V UPTD SD Negeri 145 Barru - Hasnah Hasnah; Fajar Fajar; Nurdini Fajriyanti (Universtas Negeri Makassar, 2022)
This study examines the application of the Show and Tell learning method on advertising materials to improve the speaking skills of students class V UPTD SD Negeri 145 Barru. The approach used is a qualitative approach and the type of research is Classroom Action Research (CAR). The implementation of this research action was carried out in 2 cycles starting with pre-action activities then in each cycle consisting of 4 stages which included planning, implementation, observation, and reflection. Meanwhile, to find out the process of applying and improving students' speaking skills, the researchers used observation sheets and performance tests. The subjects in this study were students of class V UPTD SD Negeri 145 Barru in the academic year 2020/2021, which amounted to 22 students consisting of 10 boys and 12 girls. Data analysis was carried out during and after data collection. The data analysis technique used is qualitative data analysis techniques. Based on the data obtained during the implementation of cycle I and Cycle II, it was found that the results of the research in the first cycle showed a sufficient category, and an increase in the second cycle which showed a good category and achieved the predetermined indicators. The conclusion of this study is that by applying the Show and tell learning method on advertising material, it can improve process of learning and speaking skills of the students class V of UPTD SD Negeri 145 Barru.